Multilayer assembled MFGM mimetics improve digestive fate of human milk structural lipids - Yehui Liang; Ruize Pan; Nian Liu; Xinggang Ni; Yan Yang; ZeYuan Deng; Jing Li (Food Research International, 2026)

Acclimatization of salt-tolerant bacteria in a pilot-scale biological treatment system for actual high-salinity wastewater from a chemical industrial park - Yifan Feng; Chunlei Yang; Jun Li; Xinchun Ding; Ruize Xia; Min Hu; Yechao Tian; Yang Pan; Quanxing Zhang; Aimin Li (Journal of Environmental Chemical Engineering, 2025)

Probability Stability Evaluation of Coral Reef Limestone Reef Slopes Under Earthquake - Ruize Ma; Baifeng Ji; Longya Zhang; Shuang Pan; Kaimeng Hu (Journal of Marine Science and Engineering, 2025)
With the rapid development of island construction and the frequent occurrence of natural disasters, the stability of coral reef slopes is attracting increasing attention. This study aims to assess the dynamic stability and instability risks of coral reef slopes under different earthquake intensities. Geological data were integrated, and the Newmark method and finite element analysis were employed for probabilistic stability assessment and permanent displacement evaluation, leading to the development of a validated model for slope stability assessment. The study explored the effects of varying earthquake intensities on slope stability. Results indicate that the stratified structure significantly influences stability. Reef limestone slopes exhibited higher stability, whereas multi-layered slopes, due to looseness, were less stable. Both slope types remained stable under static conditions. Earthquake intensity substantially impacted stability, with multi-layered slopes showing instability probabilities of 48% and 100% under peak ground accelerations (PGA) of 0.3 g and 0.4 g. Under extreme seismic conditions, the permanent displacement of multi-layered coral reef slopes significantly increased. This study aims to fill the gap in previous research by incorporating the random distribution of stratigraphic parameters, conducting probabilistic stability analysis based on the random distribution of geological parameters, and thereby providing references for island reef engineering construction.

The influence of temperature induced changes in the composition of MFGM on membrane phase transition and nanomechanical properties - Ruize Pan; Yingchao Huang; Teng Wei; Liufeng Zheng; Zhenying Hu; Jingjing Duan; Xian Hao; Zeyuan Deng; Jing Li (Food Research International, 2025)